2015
DOI: 10.1007/s00436-015-4842-z
|View full text |Cite
|
Sign up to set email alerts
|

Should we abandon quinine plus antibiotic for treating uncomplicated falciparum malaria? A systematic review and meta-analysis of randomized controlled trials

Abstract: In this study, we compared the efficacies and adverse effects of quinine plus antibiotics and other anti-malaria drugs on treating uncomplicated falciparum malaria. By systematically searching the major databases PubMed, Embase, and the Cochrane Library, 14 randomized controlled trials (RCTs) including 1996 cases were identified. Then, we performed a systematic review and cumulative meta-analysis on these data. The primary outcome of these treatments was parasite failure at day 28. There was no significant dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 23 publications
0
9
1
1
Order By: Relevance
“…However, in the treatment of uncomplicated falciparum malaria in children, we found PCRadjusted ACPR rates of 44% with quinine plus clindamycin and 97% with artemether-lumefantrine on day 28 after treatment. This is inconsistent with the ndings of the QUINACT trial or the review by Song et al [14,17]. In the QUINACT trial, quinine plus clindamycin had similar e cacy as artesunate plus amodiaquine and artemether-lumefantrine as rescue treatment for recurrent falciparum malaria in children [17].…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…However, in the treatment of uncomplicated falciparum malaria in children, we found PCRadjusted ACPR rates of 44% with quinine plus clindamycin and 97% with artemether-lumefantrine on day 28 after treatment. This is inconsistent with the ndings of the QUINACT trial or the review by Song et al [14,17]. In the QUINACT trial, quinine plus clindamycin had similar e cacy as artesunate plus amodiaquine and artemether-lumefantrine as rescue treatment for recurrent falciparum malaria in children [17].…”
Section: Discussionmentioning
confidence: 82%
“…In the QUINACT trial, quinine plus clindamycin had similar e cacy as artesunate plus amodiaquine and artemether-lumefantrine as rescue treatment for recurrent falciparum malaria in children [17]. A review found no signi cant difference in e cacy between quinine plus antibiotics compared with that of ACTs [14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One systematic review of seven randomized trials found inconclusive evidence on the efficacy of quinine plus clindamycin compared with other anti-malarials (alone or in combination) in the treatment of uncomplicated falciparum malaria [ 16 ]. Another systematic review of 14 randomized trials found no difference in efficacy between quinine plus antibiotics compared with artemisinin-based and non-artemisinin-based combinations in the treatment of uncomplicated falciparum malaria [ 17 ]. There is no published study comparing the efficacy of quinine plus clindamycin with the recommended artemisinin-based combinations in the primary treatment of uncomplicated falciparum malaria.…”
Section: Introductionmentioning
confidence: 99%